Parameter Adjustment of EROS Humanoid Robot Soccer using a Motion Visualization - Risnumawan, Anhar; Febrianto, Rokhmat; Sulistijono, Indra Adji; Kusumawati, Eny (Journal of Computer, Electronic, and Telecommunication (COMPLETE), 2022)
Humanoid robot is a robot whose overall appearance is formed based on the human body and can interact with equipment and the environment created by humans. The robot's balance becomes fundamental in carrying out various tasks in designing humanoid robots. To deal with this, the adjustment of the humanoid robot movement is crucial in this work, research related to the virtual visualization of robots. Virtual robot visualization can be done by creating a simulator that contains dynamic parameters, including the physics of the robot. With the simulation containing dynamic parameters, the humanoid robot movement can be tried many times until the robot movement is robust. Applying the URDF (Unified Robot Description Format) model to the Gazebo simulator, which is supported by the ROS (Robot Operating System) framework, can make a simulator with dynamic parameters mimicking a real environment. In order to make a robust robot motion, feedback is needed in position and torque to find out the difference between simulation and reality. On the other hand, simulations can be done without cost or risk and, most importantly, mimic the actual robot soccer environment.